14C and Marine Reservoir Effect in Archaeological Samples from the Northeast Gulf of California. Issue 5 (2015) - Dettman, David L; Mitchell, Douglas R; Huckleberry, Gary; Foster, Michael S
Abstract : Previous studies of live-collected pre-weapons testing mollusk shells in the northern Gulf of California have demonstrated that the local radiocarbon reservoir effect (ΔR) is large and highly variable. To test the validity of this observation for paired charcoal and shell samples from archaeological contexts, we dated samples from four shell midden locations and six midden layers from the eastern shoreline of the Gulf of California near Puerto Peñasco, Sonora, Mexico. Dated charcoal samples were small twigs or brushy plants used to cook shellfish and the shells dated within each midden showed signs of burning. Ages range from approximately 5700 to 1900 cal BP. The offset between the modeled marine 14 C age for calibrated ages of the middens and measured shell 14 C age (ΔR) averaged 425 yr with a standard deviation of 115 yr.